Medical tourism trends in the United Kingdom 2000-2016: Global economic crisis, migration and UK expats under consideration. Issue 1 (17th December 2019) - Pagán, Ricardo; Horsfall, Daniel
Abstract : Purpose: The purpose of this study is to investigate the inbound and outbound medical tourism in the UK to determine if the UK can be considered as a net exporter of health services as well as the impact of the 2007 global economic crisis, diaspora populations and the number of UK expats on medical tourism figures. Design/methodology/approach: Using microdata drawn from the International Passenger Survey (2000-2016), the authors estimate the flows, number of nights and expenditure of tourists looking for medical treatment who complete international visits of less than 12 months' duration to and from the UK. The authors also analyse the main destinations of UK residents, the country of origin of overseas residents and the particular case of British expats. Findings: The results show the upward trend of inbound and outbound patients, the strong seasonality in outbound patients, and the significant increase in the levels of expenditure of overseas residents since 2005. Poland, France, Hungary and India are the chosen countries by UK residents to be treated, whereas Irish Republic, Spain, France, Gibraltar and the United Arab Emirates are the main countries providing inbound health patients. However, the processes of migration explain full or partly the inbound and outbound flows found for some countries. Originality/value: This study offers a critical insight into inbound and outbound medical flows, demonstrating both the scope for and limitations to market development in this area.